Réponses

2013-06-17T18:50:25+02:00

 (-3)-(-5)=2

 (+18)-(+5)=13

 (-5)-2=-7 

 3-(-12)=15

(+7)-(+13)=-6 

(-12)-(-8)=-4

-8+3.5=-5,5

(-12)-38=-50

(-5)-(+6)=-11

(+9)-(-3)=12

(-11.3)-15.4=-26,7

-27-40=-67

 

 

 

2013-06-17T18:53:00+02:00

(-3)-(-5)=-3+5

            = 2

 (+18)-(+5)=18+(-5)

                 = 13

 (-5)-2=-5+(-2)

          = -7

 3-(-12)=3+12

           =15

 (+7)-(+13)=7+(-13)

                =  -6

 (-12)-(-8)=-12+8

              = -4

 -8+3.5= -4.5

 (-12)-38=-12+(-38)

              = -50

 (-5)-(+6)=-5+(-6)

               = -11

 (+9)-(-3)=9+3

              = 12

 (-11.3)-15.4=-11.3+(-15.4)

                   = -26.7

 -27-40=-27+(-40)

            = -67

 

VOILA!!